Vplivni dejavniki pojava in jakosti vetroloma na območju Črnivca - Klopčič, Matija (Gozdarski vestnik, 2013)
In Central Europe wind was recognized as the main abiotic factor of forest stand dynamics. It mostly causes low-severity disturbances, but also disturbances of moderate severity are frequent, whereas high-severity disturbances are rare. However, one such disturbance happened at the broader area of the mountain pass Črnivec in the year 2008. In the study, Kendall tau-b correlation coefficient and binary logistic regression were used to find out whether the data from permanent sample plots (PSP) can be used to analyze the occurrence of a windthrow on a study site. Various stand and site factors were statistically significantly associated with the damage level in aparticular stand. The highest damage level within the development phases was recorded in mature stands, whereas no damage was documented in regeneration, thicket stage and pole stage stands. Stands with a higher share of conifers were more severely damaged than those with a lower share of conifers. The most severe damages were found in stands with < 25 % of broadleaves in stand volume, while in stands with the share of broadleaves Ž 75 % no damage was registered. The explanatory model of windthrow occurrence at PSP level included seven variables: altitude, exposition, slope, bedrock type, and stand volume of spruce, fir and beech, respectively. Additionally, the acquired results were discussed and some forest management guidelines were proposed.
Keywords: vetrolomi; abiotski dejavniki; smreka; Črnivec; Slovenia; Slovenija